Fumigant Toxicity and Oviposition Deterrent Activity of Volatile Constituents from Asari Radix et Rhizoma against Phthorimaea operculella (Lepidoptera: Gelechiidae). Issue 6 (11th December 2020) - Wu, Mei; Xiong, Yan; Han, Rui; Dong, Wenxia; Xiao, Chun
Abstract: Phthorimaea operculella (Zeller) is a worldwide pest of potato. Plant-borne chemicals would be potential alternatives of synthetic chemical fumigants against P. operculella in the storage. Asari Radix et Rhizoma is derived from the dry roots and rhizomes of Asarum heterotropoides Fr. Schmidt var. mandshuricum, A. sieboldii Miq. var. seoulense, or A. sieboldii . In this study, fumigant toxicity and oviposition deterrent of volatile constituents from ARR, δ-3-carene, γ-terpinene, terpinolene, eucarvone, 3, 5-dimethoxytoluene, and methyleugenol were tested against P. operculella . The preliminary verification of preventive and control effects of eucarvone, 3, 5-dimethoxytoluene and methyleugenol on P. operculella was carried out by simulating warehouse experiments. The results indicated that the six compounds above had fumigation toxic effects on the adults and eggs of P. operculella . Among them, δ-3-carene, γ-terpinene, and terpinolene had weaker fumigation effects than those of eucarvone, 3, 5-dimethoxytoluene, and methyleugenol. The LC50 values of eucarvone, 3, 5-dimethoxytoluene, and methyleugenol against adult P. operculella were 1.01, 1.78, 1.51 mg/liter air, respectively. The LC50 values against egg P. operculella were 1.09, 0.55, 0.30 mg/liter air, respectively. The oviposition deterrent experiment showed that only methyleugenol (at 5 and 1 mg/ml) and eucarvone (5 mg/ml) had a substantial oviposition deterrent effect. The simulated warehouse experiment verified that methyleugenol, eucarvone, and 3, 5-dimethoxytoluene protected potatoes from P. operculella and demonstrated that methyleugenol had the best preventive and control effects. It was concluded that methyleugenol was the active ingredient with the most potential in the volatiles from ARR on P. operculella control and merit further study as botanic fumigant.